Visual studio 2013 cookbook : over 50 simple but incredibly effective recipes to get you up and running with the powerful features of visual studio 2013 /: over 50 simple but incredibly effective recipes to get you up and running with the powerful features of visual studio 2013. (2014) - Martin, Jeff; Banks, Richard
No abstract available